Quantum information, cognition, and music - Dalla Chiara, Maria L.; Giuntini, Roberto; Leporini, Roberto; Negri, Eleonora; Sergioli, Giuseppe (Frontiers in Psychology, 2015)
Parallelism represents an essential aspect of human mind/brain activities. One can recognize some common features between psychological parallelism and the characteristic parallel structures that arise in quantum theory and in quantum computation. The article is devoted to a discussion of the following questions: 1) a comparison between classical probabilistic Turing machines and quantum Turing machines; 2) possible applications of the quantum computational semantics to cognitive problems; 3) parallelism in music.